"Clever Little Bag" Green Packaging Innovation from Puma - Sutanto, Shienny Megawati (VCD: Journal of Visual Communication Design, 2018)
"Clever Little Bag" a green packaging innovation from Puma. The needs for packaging products in the retail business has taking its toll for the environment due to the large amount of natural resources used and residual packaging waste. Puma, shoe manufacturer are trying to reduce this effects by innovating "Clever Little Bag". This research aims to analyze how "Clever Little Bag" succeeds in reducing Puma's carbon footprint significantly.